Institutional Responses to Campus Sexual Assault: Examining the Development and Work of A Multidisciplinary Team. Issue 3 (27th May 2019) - Olomi, Julie M.; DePrince, Anne P.; Gagnon, Kerry L.
ABSTRACT: Responding to campus sexual assault can involve complex processes and procedures that span campus, criminal justice, and community-based institutions, particularly when there are co-occurring Title IX and criminal investigations. This study investigated the development of a multidisciplinary team (MDT) that involved campus, criminal justice, and community-based institutions seeking to improve coordinated responses to campus sexual assault. Data included observations of MDT monthly meetings over 16 months as well as individual interviews with MDT members. Transcripts of the MDT meetings and individual interviews were coded to capture major themes. The MDT meetings were dynamic and flexible with a structure that involved intentional agenda setting along with responsiveness to current events and collaborative processes. The MDT invested more time during the meetings addressing the complexity of navigating existing procedures than developing new protocols. Individual interviews with MDT members highlighted logistical challenges that were relevant to MDT effectiveness, such as consistent attendance, supervisor legitimacy, and differences in stakeholder priorities. Implications for future MDT work are discussed.